2019
DOI: 10.5812/semj.83771
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Health Problems Among Primary and Secondary School Teachers: A Cross-Sectional Study

Abstract: Background: It is generally assumed that teachers lead healthy lifestyles; meanwhile, due to their specific working conditions, they stand among occupational groups exposed to a wide variety of health hazards associated with their profession. Objectives: This study aimed to investigate the prevalence of work-related health problems in the teaching profession of Shiraz, Iran. Methods: This cross-sectional study was conducted among 508 primary and secondary school teachers in Shiraz. The participants were chosen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…As in the online, blended, and offline modes of teaching, teachers experience these stressors and extended online teaching somehow sprouted the MSD symptoms due to repetitive stresses, prolonged acquired postures, etc. Various studies have shown that teachers are one of the occupational groups subjected to workrelated musculoskeletal disorder (WRMSD)and are generally unaware of the factors leading to these hazards such as poor posture, poor ergonomics, and other factors like that [9].Therefore, this study aims to find the association between ergonomics and musculoskeletal disorders (MSD) among school teachers.…”
Section: Introductionmentioning
confidence: 99%
“…As in the online, blended, and offline modes of teaching, teachers experience these stressors and extended online teaching somehow sprouted the MSD symptoms due to repetitive stresses, prolonged acquired postures, etc. Various studies have shown that teachers are one of the occupational groups subjected to workrelated musculoskeletal disorder (WRMSD)and are generally unaware of the factors leading to these hazards such as poor posture, poor ergonomics, and other factors like that [9].Therefore, this study aims to find the association between ergonomics and musculoskeletal disorders (MSD) among school teachers.…”
Section: Introductionmentioning
confidence: 99%